Bulging initiation and propagation in fiber-reinforced swellable Mooney–Rivlin membranes - Heiko Topol (14156889) (2021)
This article considers a thin-walled hollow cylinder, which is composed of a fibrous and swellable hyperelastic material. The fibers are arranged in two families and they are taken to be parallel within each fiber family. The two fiber families are also assumed to be mechanically equivalent and symmetrically disposed in the ground substance material. At each instant of the homogeneous swelling, the material is taken to be incompressible. This article studies the interplay of swelling, fiber orientation, and the mechanical properties of the constituents on the initiation as well as on the axial propagation of bulging. Other Information Published in: Journal of Engineering Mathematics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s10665-021-10123-5